2010
DOI: 10.1002/eji.201040360
|View full text |Cite
|
Sign up to set email alerts
|

Developmental progression of fetal HEB−/− precursors to the pre‐T‐cell stage is restored by HEBAlt

Abstract: Gene knockout studies have shown that the E-protein transcription factor HEB is required for normal thymocyte development. We have identified a unique form of HEB, called HEBAlt, which is expressed only during the early stages of T-cell development, whereas HEBCan is expressed throughout T-cell development. Here, we show that HEB À/À precursors are inhibited at the b-selection checkpoint of T-cell development due to impaired expression of pTa and function of CD3e, both of which are necessary for pre-TCR signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(34 reference statements)
1
13
0
Order By: Relevance
“…It is thought that HEB collaborates with E47 to enforce cell cycle arrest preceding the β-selection checkpoint. HEBAlt appears to function redundantly with HEB, given that ectopic expression of HEBAlt in Heb-deficient cells restored the generation of DP progenitors (241). HEB proteins may also play a role in inhibiting myeloid and NK cell fates in T cell progenitors (242).…”
Section: Distinct Programs Of T Cells and Ilcsmentioning
confidence: 98%
“…It is thought that HEB collaborates with E47 to enforce cell cycle arrest preceding the β-selection checkpoint. HEBAlt appears to function redundantly with HEB, given that ectopic expression of HEBAlt in Heb-deficient cells restored the generation of DP progenitors (241). HEB proteins may also play a role in inhibiting myeloid and NK cell fates in T cell progenitors (242).…”
Section: Distinct Programs Of T Cells and Ilcsmentioning
confidence: 98%
“…Separate transcriptional start sites in HEB give rise to canonical and shorter alternate (HEBAlt) forms (26). A developmental block in HEB 2/2 cells observed at the b-selection checkpoint can be partially restored with transgenic expression of HEBAlt, bypassing b-selection, to the DP stage, thus implicating HEBAlt as a critical regulator of early T-lineage genes (45). In addition, HEBAlt limits myeloid cell outcomes by collaborating with intracellular Notch (46).…”
Section: Dn2a/b To Dn3 Stagesmentioning
confidence: 99%
“…GATA3 is essential for CD4 gene expression, whereas Runx3 is a direct repressor of CD4 [108, 109]. We found that although HEB deficiency at the DN3 stage did not affect the expression of GATA3, transgenic reconstitution of HEB −/− cells with HEBAlt resulted in the upregulation of CD4 to generate DPs [110]. Therefore, another possibility is that HEB factors, and HEBAlt in particular, function in repressing Runx3 protein expression or activity.…”
Section: Heb In Hematopoiesismentioning
confidence: 99%
“…Furthermore, we identified pT α and CD3 signaling components as specific targets of HEBAlt during β -selection [110]. In addition, HEB −/− mice also had a defect in T-cell commitment, with compromised Notch1 function and a tendency to become DN1-like cells [106].…”
Section: Heb In Hematopoiesismentioning
confidence: 99%